COMMUNICATION THERAPY FOR APHASIA - Yuliana, Yuliana (Tomorrow's Education Journal, 2024)
Approximately one-third of patients with stroke encounter aphasia. Aphasia might reduce social networks. Therefore, aphasia management become a crucial thing. This paper aims to describe the communication therapy for aphasia. Method: This is a narrative literature review. Literature was taken from PubMed, Science Direct, and Google Scholar. The selected journal was published within 10 years (2013-2023). The types of therapy include Melodic Intonation Therapy, Constraint Induced Aphasia Therapy, Cognitive Therapy, Augmentative Communication, and AIUEO. Those types of therapy could be given in computer-based therapy. The most commonly used in Indonesia is AIUEO therapy. The patient should follow every sound and movement. This method might improve mild to moderate aphasia. In conclusion, communication therapy for aphasia is various. The choice depends on the available sources. In Indonesia, the most common type is AIUEO therapy.